2009
DOI: 10.1093/nar/gkp982
|View full text |Cite
|
Sign up to set email alerts
|

ChimerDB 2.0—a knowledgebase for fusion genes updated

Abstract: Chromosome translocations and gene fusions are frequent events in the human genome and have been found to cause diverse types of tumor. ChimerDB is a knowledgebase of fusion genes identified from bioinformatics analysis of transcript sequences in the GenBank and various other public resources such as the Sanger cancer genome project (CGP), OMIM, PubMed and the Mitelman’s database. In this updated version, we significantly modified the algorithm of identifying fusion transcripts. Specifically, the new algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 26 publications
(30 reference statements)
1
101
1
Order By: Relevance
“…Our analyses uncovered a new fusion transcript between the genes BCAM and AKT2 in one HGSC cancer sample (patient S4; Table S1). This fusion transcript is novel and has not been reported (16)(17)(18)(19). The presence of this fusion transcript in patient S4 is supported by eight paired "chimeric" reads, with one read mapping to BCAM and the other to AKT2 (Fig.…”
Section: Bcam-akt2mentioning
confidence: 71%
“…Our analyses uncovered a new fusion transcript between the genes BCAM and AKT2 in one HGSC cancer sample (patient S4; Table S1). This fusion transcript is novel and has not been reported (16)(17)(18)(19). The presence of this fusion transcript in patient S4 is supported by eight paired "chimeric" reads, with one read mapping to BCAM and the other to AKT2 (Fig.…”
Section: Bcam-akt2mentioning
confidence: 71%
“…In fact, transcription-induced chimeric RNAs, generated in normal healthy cells, without corresponding genomic rearrangements have been well recognized in the field of genetic research (Akiva, 2005;Fang et al, 2012;Gingeras, 2009;Kim DS, et al, 2007;Kim DS, et al, 2012;Kim P, et al, 2010;Kim RN, et al, 2012;Li et al, 2008;Parra, 2005;Prakash et al, 2010;Thomson et al, 2000;Zhang et al, 2012). However, the existence of transcription-induced chimeric RNAs has not been well appreciated in the cancer research field, where fusion genes play an important role in disease development, progression, and treatment (Edwards, 2010;Mitelman et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, USP9Y-TTTY15 is a transcription-induced chimeric RNA (an RNA created in normal cells by combining exons from two or more distinctly known parental genes) (Akiva, 2005;Fang et al, 2012;Gingeras, 2009;Kannan et al, 2011;Kim DS et al, 2007Kim P et al, 2010;Kim RN et al, 2012;Li et al, 2008;Parra, 2005;Prakash et al, 2010;Thomson et al, 2000;Zhang et al, 2012). Linked to this finding, we also investigated the expression of another transcription-induced chimeric RNA previously studied in prostate cancer from Western countries, SLC45A3-ELK4, of which both partner genes lie on the same chromosome within a short genomic distance (1q32) (Maher et al, 2009;Rickman et al, 2009;Zhang et al, 2012).…”
mentioning
confidence: 98%
“…In addition, chimeric RNA products with canonical splice sites and matching annotated exon boundaries are regarded as being less likely to be generated in vitro (Kim et al 2010;Al-Balool et al 2011). We found that the intragenic cases have a significantly higher percentage of candidates with canonical splice sites and matching annotated exon boundaries than the intergenic ones (P-value < 10 À13 ) (Supplemental Table 4).…”
Section: Genome Research 31mentioning
confidence: 92%
“…Generally, trans-splicing is detected by comparing the reference genomes with ESTs/mRNAs (Shao et al 2006;Li et al 2009;Herai and Yamagishi 2010;Kim et al 2010) or by next-generation sequencing (NGS) of mRNAs (RNA-seq) (McManus et al 2010;Zhang et al 2010;Al-Balool et al 2011;Fang et al 2012). Transsplicing events detected by such means may, however, include a considerable number of false positives that arise from experimental artifacts, such as template switching (McManus et al 2010;Ozsolak and Milos 2011).…”
Section: Taipei 11529 Taiwanmentioning
confidence: 99%